2020
DOI: 10.1111/dar.13069
|View full text |Cite
|
Sign up to set email alerts
|

Availability, retail price and potency of legal and illegal cannabis in Canada after recreational cannabis legalisation

Abstract: Introduction and Aims. There is little objective market data on the price or potency of legal and illegal cannabis products following recreational cannabis legalisation. Design and Methods. In the 2 months post-legalisation in Canada (November-December 2018), legal and illegal cannabis retailers were identified from government lists and online directories. The store location, price and Δ9-tetrahydrocannabinol (THC) and cannabidiol levels of dried herb and cannabis cookies were collected from retailer websites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 33 publications
0
65
0
5
Order By: Relevance
“…Indeed, among dried herb consumers who reported THC levels using a percentage, about 30% reported a value higher than 30% THC, a level that (to our knowledge) is not commonly available. 3 A recent scan conducted by our group found that < 1% of dried herb products on the legal and illegal markets in Canada exceeded 30% (unpublished data). Similar proportions reported implausible data for CBD levels in dried herb: a 2018 scan of the Canadian market found that dried herb contained an average of 2% CBD, 3 whereas respondents in the current study reported a mean of at least 20% CBD in all three jurisdictions.…”
Section: Knowledge Of Thc and Cbd Levelsmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, among dried herb consumers who reported THC levels using a percentage, about 30% reported a value higher than 30% THC, a level that (to our knowledge) is not commonly available. 3 A recent scan conducted by our group found that < 1% of dried herb products on the legal and illegal markets in Canada exceeded 30% (unpublished data). Similar proportions reported implausible data for CBD levels in dried herb: a 2018 scan of the Canadian market found that dried herb contained an average of 2% CBD, 3 whereas respondents in the current study reported a mean of at least 20% CBD in all three jurisdictions.…”
Section: Knowledge Of Thc and Cbd Levelsmentioning
confidence: 96%
“…3 A recent scan conducted by our group found that < 1% of dried herb products on the legal and illegal markets in Canada exceeded 30% (unpublished data). Similar proportions reported implausible data for CBD levels in dried herb: a 2018 scan of the Canadian market found that dried herb contained an average of 2% CBD, 3 whereas respondents in the current study reported a mean of at least 20% CBD in all three jurisdictions. This poor awareness of cannabinoid levels is consistent with a previous study in which the majority of respondents believed that low-and high-THC strains of cannabis contained ‡ 20% and ‡ 40% THC-concentrations reflective of high-THC strains and exceeding those in existing strains, respectively.…”
Section: Knowledge Of Thc and Cbd Levelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent estimates in the Canadian market suggest similar (or greater) increases in the potency of cannabis. For example, one study that tracked the potency of legal and illegal cannabis products for two months following the federal legalization of non-medical cannabis use found a mean THC concentration of 16.1% in the legal market and 20.5% in the illegal market ( 41 ). Given that the global mean THC potency of cannabis was approximately 1–2% just a few decades ago ( 36 ), the emergence of dried cannabis plant material with 20% THC or more presents a serious public health concern, especially in the absence of a proportional increase in CBD levels.…”
Section: Diversification Of Cannabis Products and The Potential Rise mentioning
confidence: 99%
“…Some data likewise suggested changes in frequency of use following recreational cannabis legalization in the U.S. with findings showing a small increase in adolescent CUD and increases in past-month cannabis use, past-month frequent cannabis use, and past-year CUD among adults over 26 years (8). Of note, studies, furthermore, suggest that cannabis has grown more potent as measured by the proportion of D 9 -tetrahydrocannabinol (THC) content in relation to cannabidiol (CBD) content (THC to CBD ratio) (9,10). Accordingly, with policy changes, there has been increased attention into cannabis-related harms such as motor vehicle accidents, emergency medical attendances and hospitalizations, severe mental disorders (SMD) as well as suicides (1,7).…”
Section: Introductionmentioning
confidence: 99%